2007
DOI: 10.1021/jp0743929
|View full text |Cite
|
Sign up to set email alerts
|

Facile SN2 Reaction in Protic Solvent:  Quantum Chemical Analysis

Abstract: We study the effects of protic solvent (water, methanol, ethanol, and tert-butyl alcohol) and cation (Na+, K+, Cs+) on the unsymmetrical SN2 reaction X- + RY --> RX + Y- (X = F, Br; R = CH3,C3H7;Y = Cl, OMs). We describe a series of calculations for the S(N)2 reaction mechanism under the influence of cation and protic solvent, presenting the structures of pre- and postreaction complexes and transition states and the magnitude of the activation barrier. An interesting mechanism is proposed, in which the protic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 49 publications
6
47
0
Order By: Relevance
“…The other OH group interacts with the mesylate leaving group, thus helping it to detach from the reactant. The calculated energy barrier (E°= 18.6 kcal mol À1 , G°(100 8C) = 19.9 kcal mol À1 ) for the reaction with KF in tetraethylene glycol is much lower than even those calculated by similar methods for the same reaction with cesium and tetra-n-butylammonium fluoride in tert-butyl alcohol and ethylene glycol; [11] [Cs [13] Replacing one hydroxy group of tetraethylene glycol by a methoxy group (see Figure S2) is calculated to increase the activation barrier significantly (E°and G°by 1.2 and 1.7 kcal mol À1 , respectively): this increase is due to the much lower acidity and tenuous interactions of OCH 3 with the leaving group compared with OH, which is in agreement with the experimental observation of a corresponding decrease in the reaction rate (see Scheme 2). In solvents containing two terminal OCH 3 groups, the reactant tends to separate away from the "loose" solvent molecule, with no prereaction complex being formed.…”
mentioning
confidence: 69%
“…The other OH group interacts with the mesylate leaving group, thus helping it to detach from the reactant. The calculated energy barrier (E°= 18.6 kcal mol À1 , G°(100 8C) = 19.9 kcal mol À1 ) for the reaction with KF in tetraethylene glycol is much lower than even those calculated by similar methods for the same reaction with cesium and tetra-n-butylammonium fluoride in tert-butyl alcohol and ethylene glycol; [11] [Cs [13] Replacing one hydroxy group of tetraethylene glycol by a methoxy group (see Figure S2) is calculated to increase the activation barrier significantly (E°and G°by 1.2 and 1.7 kcal mol À1 , respectively): this increase is due to the much lower acidity and tenuous interactions of OCH 3 with the leaving group compared with OH, which is in agreement with the experimental observation of a corresponding decrease in the reaction rate (see Scheme 2). In solvents containing two terminal OCH 3 groups, the reactant tends to separate away from the "loose" solvent molecule, with no prereaction complex being formed.…”
mentioning
confidence: 69%
“…Thexyl alcohol was included due to a report by Lee et al 30 that showed the addition of alcohol to the reaction medium facilitates the radiofluorination SN 2 -process, and the report by Javed et al 31 that showed a substantial increase in fluorination efficiency of [ 18 F]Fallypride when using this solvent mixture compared to pure MeCN. Reactions were performed in a sealed vial, heated to 110°C for 7 minutes using a Peltier heater.…”
Section: Resultsmentioning
confidence: 99%
“…SN 2 substitution is improved with alcohol as a co-solvent, perhaps by inclusion in intermediate complex formation as determined by Oh et al 30 (not shown on scheme).…”
Section: Figurementioning
confidence: 91%
“…Since most S N 2 reactions occur in solution, a large number of these studies have been devoted to the solvent effects [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. One of these effects that has been broadly examined is H-bonding via protic solvents that lowers the energy of an anionic nucleophile relative to the transition state, in which the charge is more diffuse, and results in an increase of activation energy [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…One of these effects that has been broadly examined is H-bonding via protic solvents that lowers the energy of an anionic nucleophile relative to the transition state, in which the charge is more diffuse, and results in an increase of activation energy [1,2]. In the last few years, many studies have been conducted on reducing this unfavorable effect [40][41][42][43][44][45][46][47][48]. Lee and co-workers indicated that in the form of an ion pair (M + X À ), protic solvent molecule acts as a bifunctional solvent.…”
Section: Introductionmentioning
confidence: 99%